Effects of CO2 injection factors on preventing spontaneous coal combustion in coal mine gobs: a simulation approach - Fan, Jiafeng (Frontiers in Earth Science, 2023)
The spontaneous combustion of residual coal in gob seriously threatens the safety of coal mining. Injecting CO2 into the gob not only prevent the residual coal from spontaneous combustion but also realize CO2 storage in the mined areas. Injection flux and burial depth of the port are crucial for CO2-preventing fire in coal mine gob. In this study, the distribution of the oxidation zone in Tanyaoping coal mine was field-measured and the coal oxidation kinetic model was built by adiabatic test. Then, a 3-D mathematical model was constructed based on the conditions of 5011 working face by COMSOL Multiphysics. Furthermore, the coupled effects of the two factors on the distribution of oxidation zone were investigated. Increases in both injection flux and burial depth result in a decrease in the oxidation zone volume. The reasonable ranges of injection flux and burial depth are 540-720 m3·h-1 and 30-40 m, respectively. These results provide some guidelines on how to prevent the spontaneous combustion of residual coal in mine gobs.